Ambient insect pressure and recipient genotypes determine fecundity of transgenic crop‐weed rice hybrid progeny: Implications for environmental biosafety assessment. (2nd March 2016) - Xia, Hui; Zhang, Hongbin; Wang, Wei; Yang, Xiao; Wang, Feng; Su, Jun; Xia, Hanbing; Xu, Kai; Cai, Xingxing; Lu, Bao‐Rong
Abstract: Transgene introgression into crop weedy/wild relatives can provide natural selective advantages, probably causing undesirable environmental impact. The advantages are likely associated with factors such as transgenes, selective pressure, and genetic background of transgene recipients. To explore the role of the environment and background of transgene recipients in affecting the advantages, we estimated the fitness of crop‐weed hybrid lineages derived from crosses between marker‐free insect‐resistant transgenic ( Bt/CpTI ) rice with five weedy rice populations under varied insect pressure. Multiwayanova indicated the significant effect of both transgenes and weedy rice genotypes on the performance of crop‐weed hybrid lineages in the high‐insect environment. Increased fecundity was detected in most transgene‐present F1 and F2 hybrid lineages under high‐insect pressure, but varied among crop‐weed hybrid lineages with different weedy rice parents. Increased fecundity of transgenic crop‐weed hybrid lineages was associated with the environmental insect pressure and genotypes of their weedy rice parents. The findings suggest that the fitness effects of an insect‐resistant transgene introgressed into weedy populations are not uniform across different environments and genotypes of the recipient plants that have acquired the transgene. Therefore, these factors should be considered when assessing the environmental impact of transgene flow to weedy or wild rice relatives.